FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN SINDROM FRAILTY PADA PENDERITA DM TIPE 2 LANSIA DI RSUD SYEKH YUSUF GOWA - Indo Nurul; Ruslan Hasani; Heriansyah Heriansyah; Nasrullah Nasrullah; Masdiana Masdiana (Media Keperawatan:Politeknik Kesehatan Makassar, 2019)
Frailty syndrome is often correlated with the appearance of pathological conditions in elderly age. Frailty syndrome occurs in 30% of the population over 80 years and 7% in the population above 65 years with a higher incidence of women. The purpose of this reserach was to determine what factors are related to the incidence of Frailty Syndrome in elderly Type 2 DM sufferers. The type of this research is a correlational descriptive research, where the researchers conducted the research with a cross sectional approach. The population in this research were all the patients with type 2 DM who were in Regional Public Hospital (RSUD) Syekh Yusuf Gowa, with the population of 152 people. The sample in this research amount 40 people with a non-probability sampling method with purposive sampling technique. This research was conducted at the Regional Public Hospital (RSUD) Syekh Yusuf Gowa on April 29th- May 29th 2019. The results of this research found that the value of medication adherence with p= 0,003, physical activity with p= 0,000, and diet with p= 0,000. The conclusion of this reserach is; there is a relationship between medication adherence with frailty syndrome, there is a relationship between physical activity with frailty syndrome, and there is a relationship between dietary habit with frailty syndrome